Effect of Genotype and Maternal Affective Disorder on Intronic Methylation of FK506 Binding Protein 5 in Cord Blood DNA - Duis, Jessica; Cox, Olivia H.; Ji, Yuelong; Seifuddin, Fayaz; Lee, Richard S.; Wang, Xiaobin (Frontiers in Genetics, 2018)
A single nucleotide polymorphism (SNP: rs1360780) in FKBP5 (FK506 Binding Protein 5) has been shown to interact with exposure to childhood adversity to promote loss of methylation and increase in gene expression in adults. We asked whether rs1360780 can influence FKBP5 intronic methylation in the context of exposure to maternal affective disorders in utero. Sixty cord blood DNA samples from the Boston Birth Cohort were genotyped at rs1360780 and studied for methylation changes as they relate to genotype and exposure to affective disorders during pregnancy. Linear regression was employed to contrast the risk (TT) genotype to the heterozygous (CT) and homozygous (CC) genotypes with adjustment for potential confounders. The recessive genotype (TT) was associated with increased methylation at multiple CpGs in the FKBP5 intron 5 region (p<0.01). These findings were enhanced among cases exposed to maternal affective disorders (p=0.02). A human cell line treated with cortisol showed that changes in intron 5 CpG methylation and FKBP5 expression were inversely associated. These findings suggest that rs1360780 can influence FKBP5 intronic methylation by acting in cis as a methylation quantitative locus and highlight the impact of genotypic risk on methylation in utero. Additionally, prenatal stress exposure compounded with the risk genotype may lead to a compensatory increase in methylation.